West/border/road : nation and genre in contemporary Canadian narrative - Roberts, Katherine Ann, 1968- (McGill-Queen's University Press, 2018)
"Understanding how Canadian culture negotiates its rapport with American genres has never been more timely given the continued vertical integration of the North American entertainment industry and new modes of technological delivery that challenge Canadian content regulations. West/Border/Road offers an interdisciplinary and cross-generic analysis of contemporary Canadian manifestations of three spatially-coded American genres: the western, the border and the road. It situates close readings of literary, film and television narratives from both English-Canada and Quebec within a larger context of Canadian generic borrowings and innovation. Using an approach of critical nation theory, Roberts calls upon canonical works in Canadian studies, theories of genre and a wide-range of scholarship from related fields (border studies, culture studies, film studies) to examine how genre is appropriated and reworked (or not) in recent representative texts and how these cultural narratives can be read critically for how they engage with discourses of contemporary Canadian nationness. In readings that elucidate Guy Vanderhaeghe's re-writing of the codes of the historical western to include the trauma of Aboriginal peoples, Aritha van Herk's playfully spoof of American western iconography, the politics and perils of the representation of the Canada-U.S. border in CBC-produced crime television and how the road genre inspires and constrains the Québécois and Canadian road movie, Roberts provides a nuanced perspective on Canadian engagement with American cultural forms that are imported but never foreign. A reminder of the power and limitations of American genres, West/Border/Road is a compelling account of how the asymmetrical embeddedness of the Canadian-American cultural relationship is negotiated in today's texts."--